A coupled CFD approach for performance prediction of fin-and-tube condenser. (16th September 2020) - Ma, Xiaowei; Zhang, Quan; Wang, Jiaqiang; Yu, Yuebin
Abstract: This article developed a novel numerical model for accurately predicting the thermal performance of fin-and-tube condenser, which coupled heat transfer between the air and refrigerant side. The heat exchange calculation between the air and refrigerant side was alternatively performed by coupling the tube wall temperatures. Meanwhile, the air side flow and heat transfer characteristics among the fin plates were achieved by porous media approach. Based on this model, the numerical studies were conducted for investigating the effects of air inlet temperature and frontal velocity on the thermal performance of such heat exchanger. Results showed that the predicted overall heat transfer rate was within the range of ±10% compared with the experimental data. It indicated that the porous media model was able to predict the thermal and flow characteristics of air side in a fin-and-tube condenser, and furthermore it could be used for the optimal design of such heat exchanger.